THE ROLE OF ACCOUNTING INFORMATION IN THE SUCCESS OF SMALL & MEDIUM ENTERPRISES (SMEs) IN NORTH CAROLINA - Vassallo, James M (My University, 2024)
This study examines what accounting knowledge is lacking in the average SME business owner, and how those gaps may inhibit business success. This research found that business owners were able to complete algebraic problems relating to breakeven analysis and inventory control but struggled in correctly identifying accounts, performing journal entries, and understanding the importance of internal controls. These findings highlight a lack of basic accounting knowledge such as bookkeeping and financial statement comprehension. Additionally, this research uncovered that most business owners are not directly involved in the accounting of their business, instead utilizing the professional services of a certified public accountant. While the sample size was limited, the results emphasize the potential benefit of further research in this area, to eventually provide SME owners with the knowledge and financial literacy necessary to gain competitive advantage and grow sustainably.
Keywords: Accounting; Small Business; SME